Heavy metals in shrimp pond sludge, water and muscles - Ling, Teck Yee; Malini, M.R.; Lee, Nyanti (COSTAM and ASM, 2008)
Sarawak is a key producer of cultured black tiger shrimp (Penaeus monodon). However,knowledge on heavy metals in shrimp pond is scarce in literature. Therefore, concentrations of selected heavy metals (In, Cu, Mn, Cd) in shrimp pond sludge, pond water, shrimp feed, and shrimp muscles from two farms in different locations were investigated. Results indicated that heavy metals concentrations of sludge, though elevated, did not exceed the standard established. Cu in the sludge was significantly correlated with the feed and the soil. Pond water heavy metals were less than 0.2 mgL except for Mn in Farm 2. In in the water was highly correlated with In in the feed. Even though Cu in the Farm 2 feed was six times that of Farm 1, there was no significant difference in the muscles.Furthermore, though Mn in sludge and water of Farm 2 were 4 and 20 times that of Farm 1, muscle Mn from Farm 2 was less than Farm 1 and concentrations were low. In the shrimp muscles, In concentration was the highest followed by Cu. The muscle concentrations of all heavy metals except Mn were not significantly correlated with that in the feed, sludge or water indicating the ability and selectivity of shrimp to regulate heavy metals. The concentrations of Zn, Cu and Cd in the shrimp muscle did not exceed the maximum permissible limits of the Malaysian Food Act.